Gadjah Mada Stroke Algorithm - Development and validity for distAngushing intracerebral hemorrhagic stroke with acute ischemic stroke or infarction stroke - Rusdi Lamsudin, Rusdi Lamsudin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A prospective study on 229 acute stroke patients was conducted to develop a Gadjah Mada Stroke Algorithm (GMSA). This algorithm was proposed as a clinical strategy for distinguishing intracerebral haemorrhage from acute ischaemic or infarction stroke after onset of stroke in 3 hospitals in Yogyakarta from 16th December 1989 until 15th November 1991. The following investigations have been made: (a) interobserver reliability for questionnaire and clinical examination of stroke patients, (b) interobserver reliability in the interpretation of CT-Scans of stroke patients, (c) validity of every clinical symptom against CT-Scans to define intracerebral haemorrhagic stroke, and (d) validity of seven multiple parallel tests against CT-Scans to define intracerebral haemorrhagic stroke. The GMSA was developed by one of seven multiparallel tests which has the highest validity. A multivariate statistical analysis and validate study showed that decreasing consciousness, headache, and Babinskis reflex at the onset are significantly related to intracerebral haemorrhagic stroke. This study showed that the GMSA was reliable and valid for distinguishing intracerebral haemorrhagic stroke from acute ischaemic or infarction stroke.Key words: Gadjah Mada stroke algorithm - diagnostic test - intracerebral haemorrhagic stroke